Predictors of difficult pediatric intravenous access in a community Emergency Department. Issue 6 (November 2015) - Petroski, Adam; Frisch, Adam; Joseph, Nicole; Carlson, Jestin N.
Background: Successful intravenous (IV) placement is important in the care of the acutely ill and injured pediatric patient. There are little data that exist regarding predicators of difficult IV access in pediatric Emergency Department (ED) patients who present to community EDs. Methods: We retrospectively analyzed all pediatric charts for the calendar year 2012 from a single community teaching hospital. We identified all cases with patients less than 18 years of age in whom an IV or IV medications were ordered. We defined difficult IV access as those requiring more than one attempt, or those where the IV team was required to place the IV. We identified patient, provider, and procedural characteristics. Data were analyzed using descriptive statistics and univariate logistic regression to determine the odds ratio (OR) for predictors of difficult IV access. Results: We identified 652 patients, 607 (93%) without difficult access and 45 with difficult access. Increasing age [OR 0.94 (0.89-0.99) p = 0.017] was associated with decreased odds of difficult IV access. IVs attempted in the hand [OR 3.02 (1.06-8.58) p = 0.039] and lower extremity [OR 7.82 (2.27-26.91) p = 0.001)]) were associated with greater odds of difficult access than the antecubital fossa. Non-black/non-white race [2.37 (1.1-5.12) p = 0.028] was also associated with difficult IV access. Other factors (sex, IV catheter size, and so on) were not associated. Conclusions: In this retrospective study of pediatric patients in a community ED, decreasing age, non-black/non-white race, and IV attempt location (hand and lower extremity vs. antecubital fossa) were associated with greater odds of difficult IV access.